Can the Profitability of Medical Enterprises Be Improved After Joining China's Centralized Drug Procurement? A Difference-in-Difference Design - Hua, Yu-Fei; Lu, Jin; Bai, Bing; Zhao, Han-Qing (Frontiers in Public Health, 2022)
This paper explores that impact of joining China's centralized drug procurement on the profitability of medical enterprises by difference-in-difference model. When centralized procurement can not bring enough cost savings to enterprises, the price competition caused by centralized procurement will lead to the decline of enterprise profits. In the short term, The negative impact of China's drug centralized procurement policy on the net profit of enterprises is not obvious in the year when enterprises win the bid. After the government officially purchases from pharmaceutical enterprises, the negative impact of China's drug centralized procurement policy on the net profit of enterprises begins to appear gradually. Therefore, for generic drug manufacturers, increase R & D investment and have their own heavy products of original drugs as soon as possible, so as to enhance their core competitiveness.